Vorstellung der Masterarbeit: Facing Religious Diversity and Secularisation – About the Future of Denominational Religious Education in Compulsory School in Austria - Jakob, Jennifer (Österreichisches Religionspädagogisches Forum, 2019)
Vorstellung der Masterarbeit: Facing Religious Diversity and Secularisation